The effects of fusel oil water content reduction on performance and emissions of SI engine with fusel oil – gasoline blended fuel - Awad, Omar Ibraheem (2018)
alcohol fuels are produced from several sources and have less heating value then fossil fuel. Fusel oil is a by-product obtained through the fermentation of some agricultural products such as beets, cones, grains, potatoes, sweet potatoes, rice and wheat. The high research octane number and motor octane number (RON 106 and MON 103), high oxygen content (30.23% wt) and single boiling point of fusel oil indicated it can be used as a fuel in SI engines. On the other hand, the higher water content of fusel oil (around 10-20%) led to a lower heating value by 31% compared to gasoline. Also, the higher water content of fusel oil effect negatively on the combustion duration, thereby engine performance and emission are affected. Comprehensive analyses of the fusel oil properties, performance and emissions have been performed. The data of fusel oil-gasoline properties were analyzed statistically in different ways to indicate the effects of fusel oil before and after water content extraction on the test fuels properties. The experimental conducted with direct injection SI engine run with fusel oil-gasoline blends and pure gasoline as the baseline fuel at different open throttle valve positions (% of WOT) as engine loads and engine speeds (rpm). Response surface methodology (RSM) based multi-objective optimization was applied in this work to determine the optimal blend ratio of fusel oil –gasoline before and after water extraction (FBWE10, FBWE20, FAWE10, and FAWE20) on the performance and emissions. The heating value and carbon content of fusel oil improved significantly after extracting the water content by 13% and 7%, respectively, while the oxygen content reduced. According to the statistical analysis of test fuel properties results (fusel oil-gasoline blends), the heating value, oxygen, and carbon content have statistically significant effects on the test fuels as the fraction of fusel oil increased especially after water content extraction. The engine power has improved with the extraction of water content and the highest brake power is registered with FAWE10 under rich fuel (λ<1). The lowest brake specific fuel consumption (BSFC) is reported to be 275 g/kW.h with gasoline while the highest BSFC is with FBWE10 which is reported to be 285 g/kW.h. Furthermore, the BSFC has decreased on average by 6.8% and 1.7% with FAWE10 and FAWE20, compared to FBWE 10 and FAWE20 respectively. The water content of fusel oil led to the limitation of the engine combustion thereby the NOx emission reduced. The blended fuel has insignificant effects on brake power while the highest impact of blended fuel was on BTE and BSFC responses. The extracted water content from fusel oil (FAWE10 and FAWE20) has a statistical significance in order to increase the brake thermal efficiency (BTE), NOx emission and decrease the brake specific fuel consumption (BSFC) and HC emissions while having insignificant effects on brake power. Thus, the best solution was with 20% of fusel oil after water extraction (FAWE20) at higher load and engine speed. Finally, the validation of the results showed a good agreement with the experimental data and the maximum percentage of error which is less than 5%.The findings from this study will make significant contributions to the future applications of fusel fuel in an internal combustion engine by improving the heating value.